A highly stable polyoxovanadate-based Cu(i)–MOF for the carboxylative cyclization of CO2 with propargylic alcohols at room temperature. Issue 21 (14th October 2020) - Tian, Hong-Rui; Zhang, Zhong; Liu, Shu-Mei; Dang, Tian-Yi; Li, Zhuo; Lu, Ying; Liu, Shu-Xia
Abstract : A POVs-based Cu(i )–MOF was synthesized and utilized as a heterogeneous catalyst for the cyclization of CO2 with propargylic alcohols to obtain value-added α-alkylidene cyclic carbonates, exhibiting high catalytic activity and sustainability. Abstract : A novel polyoxovanadate-based copper(i )–organic framework, [Cu I (bib)]4 V V 4 O12 (V–Cu–MOF, bib = 1, 4-bis(1 H -imidazoly-1-yl)benzene), is facilely synthesized under mild hydrothermal conditions. The structure of the V–Cu–MOF is constructed from a cyclic V4 O12 4− polyanion cluster and a 1D chain Cu(i )–MOF ([Cu I (bib)] + ). The presence of the V4 O12 4− cluster stabilizes the Cu(i )–MOF with Cu(i ) as the center, thereby improving the stability of the V–Cu–MOF and enabling it to stably exist in various solvents and pH = 2–12 solutions. Additionally, the V–Cu–MOF as a heterogeneous catalyst can catalyze the carboxylative cyclization of CO2 and propargylic alcohols to high value-added α-alkylidene cyclic carbonates at room temperature, and the conversion and selectivity are almost 100%. More importantly, no obvious decrease in the yield of the α-alkylidene cyclic carbonate is observed after ten cycles. These results indicate the excellent catalytic activity and sustainability of the V–Cu–MOF. Research on the mechanism of the catalytic reaction suggests that the high-density Cu(i ) sites in the V–Cu–MOF are the catalytically active centers for activating the C}C bonds of propargylic alcohols. To the best of our knowledge, this is the first example of polyoxometalate-based metal–organic framework catalyst for catalyzing the conversion of CO2 to value-added α-alkylidene cyclic carbonates at room temperature.